EFFECT OF CAPTOPRIL, LOSARTAN, AND AMLODIPINE TO A MODIFIED GOLDBLATT 2K1C RATS MODELLING - Fitri Nugraha, Dyan
Background and Purposes: Diagnosis of a disease in medication has become an important matter in a determination of therapy that will be practiced to patient with renal failure condition. Captopril and losartan has become major choices of drug in hypertension patient with renal failure, but not intended to renal failure patient with renal arteri stenosis condition. Application of those drugs can aggravate the renal condition in patient. Amlodipine is a drug in calcium-cahannel blocker class, with high percentage of application. Therefore the purpose of this study to compare effect of captopril, losartan, and amlodipine on renal failure (stenosis) condition. Methods: Renal failure modelling used in rats is a modified Goldblatt 2K1C modelling. Treatment given to left kidney is by a modification of clip replacement with silk thread. There are five group of tested animal, groups of negative control, positive control, groups of captopril, losartan, and amlodipine drugs. Parameter measured are blood pressure, creatinine serum, kidney index organ, macroscopic profile and kidney histology. Results: Blood pressure parameter indicates that the three groups of drug are not significantly different, while compared to groups of negative control they are dfferent, and at measurement point of 14 th day and so on, the three groups of drug show a significant difference compared to positive control group. Creatinin serum parameter shows no significant difference at each of measurement point. Left kidney (treated kidney) index organ parameter gives a significant difference between negative control, captopril, and losartan group compared to negative control, and amlodipine group. Conclusion: Either captopril, losartan, or amlodipin are able to decrease the blood pressure in tested animals. Although, among that three groups of drug, the histology profile and organ index results show that the worst damage occur to captopril drug group.